Studies on Schismatoglottideae (Araceae) of Borneo XXXXII: Additional new species of Aridarum - Wong, Sin Yeng; Boyce, P.C; Low, Shook Ling (International Aroid Society, Inc., 2014)
Three new species of Aridarum are described and illustrated: Aridarum perplexum S. Y. Wong, S. L. Low & P. C. Boyce from Kalimantan Barat, Indonesian Borneo, Aridarum sabahense S. Y. Wong, S. L. Low & P. C. Boyce from Sabah, Malaysian Borneo, and Aridarum spissum S. Y. Wong, S. L. Low & P. C. Boyce from Sarawak, Malaysian Borneo. Together these novelties take the genus Aridarum to 24 accepted, described species. The new species inserted into an updated identification key to Aridarum species.